Alphavirus-based hepatitis C virus therapeutic vaccines: can universal helper epitopes enhance HCV-specific cytotoxic T lymphocyte responses? - Georgia Koutsoumpli; Peng Peng Ip; Ilona Schepel; Baukje Nynke Hoogeboom; Annemarie Boerma; Toos Daemen (SAGE Publishing, 2019)
Background: Antigen-specific T cell immune responses play a pivotal role in resolving acute and chronic hepatitis C virus (HCV) infections. Currently, no prophylactic or therapeutic vaccines against HCV are available. We previously demonstrated the preclinical potency of therapeutic HCV vaccines based on recombinant Semliki Forest virus (SFV) replicon particles. However, clinical trials do not always meet the high expectations of preclinical studies, thus, optimization of vaccine strategies is crucial. In efforts to further increase the frequency of HCV-specific immune responses in the candidate SFV-based vaccines, the authors assessed whether inclusion of three strong, so-called universal helper T cell epitopes, and an endoplasmic reticulum localization, and retention signal (collectively termed sigHELP-KDEL cassette) could enhance HCV-specific immune responses. Methods: We included the sigHELP-KDEL cassette in two of the candidate SFV-based HCV vaccines, targeting NS3/4A and NS5A/B proteins. We characterized the new constructs in vitro for the expression and stability of the transgene-encoded proteins. Their immune efficacy with respect to HCV-specific immune responses in vivo was compared with the parental SFV vaccine expressing the corresponding HCV antigen. Further characterization of the functionality of the HCV-specific CD8 + T cells was assessed by surface and intracellular cytokine staining and flow cytometry analysis. Results: Moderate, but significantly, enhanced frequencies of antigen-specific immune responses were achieved upon lower/suboptimal dosage immunization. In optimal dosage immunization, the inclusion of the cassette did not further increase the frequencies of HCV-specific CD8 + T cells when compared with the parental vaccines and the frequencies of effector and memory populations were identical. Conclusion: We hypothesize that the additional effect of the sigHELP-KDEL cassette in SFV-based vaccines depends on the immunogenicity, nature, and stability of the target antigen expressed by the vaccine.